Design of a Love Language Module for Adolescent Interactions in Gunung Pangilun Urban Village - Tiara Latifah Arnum; Rahma Wira Nita; Rahmawati Wae (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Adolescents require the ability to express attention, care, and appreciation appropriately to develop constructive peer relationships. However, educational resources that integrate the love language framework into adolescent peer interaction remain limited. This study aimed to develop a contextually relevant Love Language Module for adolescent interactions in Gunung Pangilun Urban Village. A research and development approach was implemented through needs analysis, product planning and development, expert validation, and product revision. The study involved 40 adolescents aged 13–18 years selected through total sampling. Data were collected using observations, interviews, and questionnaires and analyzed through descriptive quantitative techniques. The findings showed that 65.0% of the adolescents were classified in the appropriate category and 30.0% in the very appropriate category. Quality time emerged as an area requiring further reinforcement, particularly regarding attentive presence and meaningful togetherness. Expert validation yielded a score of 342 out of 360, equivalent to 95%, with an overall mean of 3.80, indicating that the module was highly feasible. These findings demonstrate that the developed module meets expert feasibility criteria and addresses adolescents’ identified interactional needs. The module provides a contextual educational and reflective resource for fostering more empathetic, supportive, and meaningful peer interactions among adolescents.